Evaluation of Ecological Plasticity and Fat Biosynthesis in Oil Flaxseed Cultivars in the Dry-Steppe Zone of Northern Kazakhstan - GORDEYEVA, Yelena; SHESTAKOVA, Nina; YATSYUK, Svetlana; ZHANBYRSHINA, Nurrsaule (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).03, 2018)
This paper presents the results of two-year field experiments on the reaction of various cultivar genotypes to the climatic conditions of cultivation on dark chestnut soils of Northern Kazakhstan. The study identifies a number of cultivar groups by productivity, which can be recommended for different cultivation conditions. It is shown that the cultivars Severny and Biryuza have high responsiveness to the improvement of cultivation conditions, while Isilkulsky, Karabalyksky 7, Lirina and Kazar react less strongly to environmental conditions, and Ilyich, Kostanay amber and VNIIMK 620 change the yield in accordance with changes in environmental conditions. The cultivars VNIIMK 620, Lirina and Karabalyksky 7 have the maximum oil content. The study also shows the reduction of oil accumulation in seeds depending on the increase in the density of planting, and the increase in moisture during the formation of seeds.